Screening of Fusarium oxysporum for Ethanol Production by Simultaneous Saccharification and Fermentation of Bagasse and Its Ethanol Production Performance - Jiajia ZHAN; Quan ZHOU; Xingyao XIONG; Zhixu ZHANG; Yaping HU; Bi LI; Zongrui CHEN; Yihang GONG; Runan HE; Dan QIN; Lu ZENG (Shipin gongye ke-ji, 2023)
In order to obtain an excellent Fusarium oxysporum strain for simultaneous saccharification and fermentation (SSF), the cellulase activity of the 14 strains of Fusarium oxysporum was determined, and Congo red plate staining and paper disintegrating tests were carried out to screen the strains, the ethanol production experiment of SSF was carried out to investigate its cellulose degradation and sugar conversion performance. The results showed that strain mh2 had strong cellulose degradation ability, its cellulase activity was 14.28 U/mL, the diameter of transparent circle was 4.5 cm, which could completely degrade the filter paper into paste. The yield of ethanol could reach 98 g/kg and 41.7 g/kg, respectively, and the conversion of ethanol could reach up to 33.36%. In addition, the activities of filter paper enzyme, endo-glucanase, β-glucanase and exo-glucanase in mh2 cellulase system were 25.63, 15.69, 19.61 and 22.44 U/mL, respectively, the degradation rate of bagasse cellulose was 25.6%, and the ethanol conversion rate of glucose and xylose was 0.443 and 0.213 g/g, respectively, the biodegradability of mh2 was 1.58, 1.17 and 3.8 times higher than that of Cs20, respectively, indicating that mh2 had good biodegradability and sugar conversion during SSF. This study can provide data for the study of SSF to enrich the resources of SSF strains and single strain to produce ethanol from lignocellulose.